Design and synthesis of quorum-sensing agonist for improving biofilm formation and the application of Acidithiobacillus thiooxidans in bioleaching - Tang, Deping; Xi, Yanpeng; Song, Wentao; Li, Mengjiao; Liu, Yali; Lin, Yanyan; Zhang, Ran; Mao, Aihong (Frontiers in Microbiology, 2024)
Currently, there are few investigations on the effect of a synthetic exogenous quorum sensing (QS) agonist on the bioleaching rate of Acidithiobacillus thiooxidans (A. thiooxidans). We created AHL (Nacyl-homoserine lactone) analogues and investigated their effects on A. thiooxidans biofilm formation, adsorption kinetics, bioleaching, and mechanism. The findings revealed that N-(3-thiolactone)dodecylamine (Y3) significantly increased the biofilm formation of A. thiooxidans in 96-well plates and sulfur sheets. Adsorption tests revealed that Y3 increased the adhesion rate, adsorption constant, and adsorption efficiency. Bioleaching tests indicated that Y3 boosted bioleaching efficiency, with Ni 2+ and Cu 2+ bioleaching rates increasing by 49.13% and 33.03%, respectively. Transcriptomic analysis revealed that Y3 increased genes associated with QS pathways and biofilm formation, particularly afeI, which was dramatically elevated 42 times. The study laid the groundwork for a better understanding of the mechanics of A. thiooxidans biofilm formation, which could help improve the potential application of A. thiooxidans in bioleaching.